The Impact of the Sri Lankan Civil War on the Stock Market Performances - Jayakody, Shashitha Gimhani (International Journal of Economics and Financial Issues, 2017)
This study examines the effects of terrorist attacks on the Sri Lankan stock market during the last phase of the civil war. The mean adjusted returns model is employed to test whether the 19 industries in the Colombo Stock Exchange exhibit varied reactions for 9 selected terrorist attacks. Using daily data over the period from July 2006 to May 2009, the event study revealed that terrorist attacks have a statistically different impact across industries. Keywords: Event study, Efficient markets, Terrorist attacks JEL Classifications: G10, G14